DANGDUT SEBAGAI MEDIA KOMUNIKASI POLITIK (Studi Etnografi Peranan Pertunjukan Dangdut dalam Pemilihan Kepala Daerah Lebak, Banten Periode 2013) - , HESTI NURRIFKA I., Mufti Nurlataifah, SIP., MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dangdut is one of the music genre well-spread in Indonesia. The historically closeness of Dangdut Music and Indonesian people makes it as one of the most favorite music genre for them. Besides, Dangdut has a unique relation in the process of politics in Indonesia. This research is based on the relation between political world in Indonesia and Dangdut Music. The existance of the Dangdut music performances in the campaign of political parties during the election time in Indonesia becomes such an obligation to do. However, in the last few years, the role of Dangdut music in the political worldhave been changed. Such as Dangdut singer who then becomes ambassador of certain political party or the candidate of regional leader and, sometime,Dangdut music become an official single for some campaigns. From these backgrounds, a research question is proposed: How is the role of Dangdut performance in the campaign of Regional Leader Election of Lebakin 2013? To answer that question, the Ethnography Method of Researchisapplied with the qualitative approach. Technical methods of collecting data are participatory observation, interviews, and documentation. The research itself started from July 16, 2013 till August 27, 2013. At the campaign of Regional Election in Region of Lebak 2013, there are three roles of Dangdut music performances. First role is as a media of the political communication. The artists or the singers who perform on the stage during the campaign become a speaker for campaign messages of the candidates whom they represent for, including through the music lyrics sung by the artists. The second role is as an entertainment. The supporters mass and the people who attend the campaign said that the existence of Dangdut music during the regional election is merely as an entertainment for them. The third role is as a mass attractant. The campaign activity that has stage performance of Dangdut on it will have higher number of supporters than those without it.